Malaysian generational cohorts in the new media era: historical events and collective memory. Issue 3 (6th May 2022) - Mustafa, Hasrina; Mukhiar, Sharifah Nadiah Syed; Jamaludin, Shariffah Suraya Syed; Mohd Jais, Norhani
Abstract: Western labeling is widely used to define a generation. However, this label was developed based on American history. Guided by Generational Cohort Theory, this research aims to define the generational cohorts of Malaysia based on historical events and collective memory. Twelve focus group interviews (FGI) were conducted. The findings revealed four generational cohorts, namely the Pre-Merdeka (Pre-Independence), Merdeka, Reformists, and Internet generations. Overall, the Pre-Merdeka generation who are in their late 70 s and early 80 s (born in 1944 and prior) clearly recounted the hardships and food scarcity during the Japanese Occupation. They care most for security and peace of the country. The Merdeka generation (50 s and 60 s years old or born between 1945 and 1964) recalled mostly various racial and political struggles during the run up to Malaysia attaining independence such as the 13th of May 1969 incident. The Reformists (30 s and 40 s age group born between 1965 and 1984) elicited memories on various national development and achievements in sports, politics, and computer technology. The Internet generation (in their 20 s or born from 1985 onwards) recalled mostly social media impact and smartphones while reminiscing on the birth of the new Malaysia in 2018. Generally, the findings reflect unique generational cohorts with distinct recollection.